2018
DOI: 10.1182/bloodadvances.2018024877
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomal regulation of lymphocyte homing to the gut

Abstract: Exosomes secreted from T cells have been shown to affect dendritic cells, cancer cells, and other T cells. However, little is known about how T-cell exosomes (T exosomes) modulate endothelial cell functions in the context of tissue-specific homing. Here, we study the roles of T exosomes in the regulation of gut-specific T-cell homing. The gut-tropic T cells induced by retinoic acid secrete the exosomes that upregulate integrin α4β7 binding to the MAdCAM-1 expressed on high endothelial venules in the gut. T exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…Due to their prominent stability, long circulating half‐life and favorable safety profile, exosomes emerge as promising drug delivery vehicles that are able to deliver cargoes into the cytoplasm with minimal toxicity . Furthermore, exosomes possess a unique “homing” effect, i.e., the ability to target the cell type from which exosomes are produced . Therefore, exosomes are poised to become a rising star as effective drug delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their prominent stability, long circulating half‐life and favorable safety profile, exosomes emerge as promising drug delivery vehicles that are able to deliver cargoes into the cytoplasm with minimal toxicity . Furthermore, exosomes possess a unique “homing” effect, i.e., the ability to target the cell type from which exosomes are produced . Therefore, exosomes are poised to become a rising star as effective drug delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The signaling cascade elicited by inflammatory mediators upregulates MAdCAM-1 expression; for example, in the gut tissues of inflammatory bowel diseases, MAdCAM-1 expression is augmented, thereby promoting the accumulation of aberrantly activated Tlymphocytes expressing integrin α4β7. The recent work by Park et al [4] revealed a new regulatory mechanism driven by exosomes secreted from the gut-tropic T lymphocytes that suppresses MAdCAM-1 expression in HEVs (Fig. 1a).…”
Section: Immune Lymphocyte Traffickingmentioning
confidence: 92%
“…Simultaneous to acquiring the ability to better home to the gut, gut tropic lymphocytes secrete exosomes that carry high levels of integrin α4β7 on the surface. Exosomal α4β7 integrins are functionally active and remain competent for binding to MAdCAM-1 [4]. When injected into mice, α4β7 integrin-expressing T-cell exosomes are preferentially distributed to the gut mucosa in an integrindependent manner, as is observed with gut-tropic T lymphocytes [4].…”
Section: Exosomoal Regulation Of Lymphocyte Homingmentioning
confidence: 98%
See 1 more Smart Citation
“…(17,22,102) Which types of recipient cells are using these mechanisms is not well delineated. If receptor-mediated endocytosis renders the specificity of the interaction between exosome and recipient cell, cell adhesion molecules will be involved (103)(104)(105)(106)(107)(108)(109)(110). Among four groups of cell adhesion molecules (CAMs) of immunoglobulin (Ig) superfamily, cadherin, integrin and C-type lectin-domain proteins (CTLD), integrins received attention as the first paper of organotropism reported that the formation of premetastatic niche was made possible by delivery of exosomes having α6β4 (for laminin) and α6β1 to the lungs and αvβ5 (for vitronectin) for the liver (111) ( Figure 8A).…”
Section: Specificity Of Exosomes Uptake and Therapeutic Effectsmentioning
confidence: 99%